Towards a 'post - public era'? Shifting frames in German and Australian higher education policy - Pick, David (Blackwell Publishing Ltd, 2008)
Higher education in Germany and Australia is being subject to pressures of market forces, internationalisation and financial constraints. This had led to both systems experiencing significant crisis and change over the past 20 years. In this paper, frame analysis is used to compare the changing policies in each nation and examine the extent to which the landscapes of each system have been transformed. It is found that higher education policy in both nations underwent significant change in the late 1980s and again in the early 2000s, impacting on system structures and institutional forms. There is now evidence of further change occurring in both nations that may mark a transition to a ‘post-public era’ in higher education. This analysis reveals a degree of convergence in the neo-liberal policy trajectories of both nations but differences in the rate and nature of the transitions taking place.